Tobacco's social and economic issues in Indonesia from 1992 to 2023 – a review to address product development - Prasetya, Bambang; Adinugroho, Teguh Pribadi; Mulyono, Ary Budi; Tampubolon, Biatna Dulbert; Wahono, Daryono Restu (International Journal of Innovative Research and Scientific Studies, 2025)
Indonesia has a distinct problem related to tobacco control because of its unique conditions and internal opposing interests. The tobacco industry is often seen as bringing substantial benefits to Indonesia, as well as having inherent cultural and heritage values. On the other hand, high and increasing tobacco use creates an economic burden from preventable diseases, threats to the demographic bonus, and other social hazards. The presence of electronic cigarettes (ECs) and various novel tobacco derivatives adds complexity to the existing problem. This study aims to gather and analyze published studies on the social and economic aspects of tobacco products from 1992 to 2023 to propose recommendations that contribute to the development of future regulations. Qualitative methods were used in this study. Specific search keywords were employed for collecting papers, which were processed for inclusion and exclusion; the selected papers were then subjected to content analysis. The findings are clustered into eight social aspects and five economic aspects. The differences between conventional and EC cigarette conditions are displayed in the MPOWER matrix, and the corresponding synthesis was then compared with proposals from existing studies and reports to produce enhanced recommendations. The conclusions emphasize the need for a tobacco master plan, efforts to diversify tobacco derivative products, voluntary initiatives from the industry to create a system that supports more responsible tobacco use, and the importance of conducting research and monitoring supported by independent funding, standards, and testing facilities to address problems and formulate appropriate policies.